Humanist algorithms for COVID-19 vaccines' distribution and its impact on business economics in the post-pandemic future - Jaime Gil-Aluja; Jaime Gil-Lafuente; Martyna Nowak (European Research on Management and Business Economics (ERMBE), 2021)
As the world is fighting against the continuous spread of the COVID-Sars-2 virus and the consequences the pandemic has brought about on economic, political and societal levels, the emergence of the vaccination programs seems to be the biggest hope for a quick return to, popularly called, the "new normal". As it is not feasible to vaccinate at the same time the whole population, the states, provinces and cities had arranged - though, admittedly, taking into consideration limited numbers of criteria - homogenous groups of citizens, who, labelled as "risk groups", have been chosen as those who will be receiving the vaccination before others, adding to the already existing feelings of chaos and shortage. We want to address the issue that despite the access to the expertise and knowledge of intradisciplinary committees, we still do not have a satisfactory answer regarding the further steps for the vaccination programs. We believe it is due to the persistence of the binary way of reasoning, with its tendency to overlook the complexity of the issue and emphasize objectivity while neglecting the subjective factors that cannot be easily quantified. For that very reason, we propose the application of the theories of uncertainty with the support of the fuzzy subset theory, which will result in the creation of the humanist algorithms of clustering of populations, allotment of different kinds of vaccine for diverse persons in the groups and, finally, ranking for the priority of vaccination. This approach will allow designing a vaccination model to that will allow to maintain, to the highest possible level, the principles of ethics, morale and solidarity, and efficiency and effectiveness.
Keywords: C55; H12; I14; I15; I18; 650; COVID-19; Fuzzy subset theory; Humanist algorithm; Theories of uncertainty; Vaccination program